Empowering Cultural Diplomacy: Indonesian International Mobility Awards (IISMA) Students on the World Stage - Putu Ratih Kumala Dewi; Ni Nyoman Clara Listya Dewi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The Indonesian International Student Mobility Award (IISMA) is a flagship program under the Merdeka Belajar Kampus Merdeka initiative, which enables Indonesian students as awardees to study at universities abroad for one semester. Designed to enhance Indonesia's education system and human resources, the program also functions as a cultural diplomacy initiative by introducing Indonesian culture to international students. This study explores the role of IISMA participants as non-state actors in cultural and exchange diplomacy, contributing to the promotion of Indonesian culture globally. Using qualitative research methods, primary data were collected through interviews with Udayana University students who had participated in the IISMA program. The study is grounded in the concepts of new public diplomacy, cultural and exchange diplomacy. Findings indicate that IISMA participants act as diplomacy agents by disseminating various elements of Indonesian culture throughout the program. This highlights the importance of the role of students and educational institutions in strengthening collaborative relations between the two countries.